THE INFLUENCE OF COLORED WORD LEARNING MEDIA ON THE READING SKILLS OF GRADE 1 ELEMENTARY SCHOOL STUDENTS - Pratiwi, Cerianing Putri; Widyaningrum, Heny Kusuma (Proceeding International Seminar of Islamic Studies, 2023)
Reading is a basic skill that must be possessed by students. Reading skills are very important for students. This study aims to determine the influence of colored word learning media on the reading ability of grade 1 elementary school students. This research included quantitative research conducted on 64 first-graders of primary school. The data retrieval technique uses a reading test. The test design used is an experimental design with the type of Postest Only Control Group Design. The data analysis technique used in this study is the t-test. The results showed the influence of colored word learning media on the reading ability of grade I elementary school students. Based on the calculation results of the t test analysis, it can be seen that significant values of 0.000 0.05.  So it is known that there is an influence of colored word learning media on students' reading skills. The average score of reading skills in the experimental class was higher than the average score of the control class that did not use colored word learning media.